Mono- and biallelic germline variants of DNA glycosylase genes in colon adenomatous polyposis families from two continents - Olkinuora, Alisa Petriina; Mayordomo, Andrea Constanza; Kauppinen, Anni Katariina; Cerliani, María Belén; Coraglio, Mariana; Collia, Ávila Karina; Gutiérrez, Alejandro; Alvarez, Karin; Cassana, Alessandra; Lopéz-Köstner, Francisco; Jauk, Federico; García-Rivello, Hernán; et al. (Frontiers in Oncology, 2022)
Recently, biallelic germline variants of the DNA glycosylase genes MUTYH and NTHL1 were linked to polyposis susceptibility. Significant fractions remain without a molecular explanation, warranting searches for underlying causes. We used exome sequencing to investigate clinically well-defined adenomatous polyposis cases and families from Finland (N=34), Chile (N=21), and Argentina (N=12), all with known susceptibility genes excluded. Nine index cases (13%) revealed germline variants with proven or possible pathogenicity in the DNA glycosylase genes, involving NEIL1 (mono- or biallelic) in 3 cases, MUTYH (monoallelic) in 3 cases, NTHL1 (biallelic) in 1 case, and OGG1 (monoallelic) in 2 cases. NTHL1 was affected with the well-established, pathogenic c.268C>T, p.(Gln90Ter) variant. A recurrent heterozygous NEIL1 c.506G>A, p.(Gly169Asp) variant was observed in two families. In a Finnish family, the variant occurred in trans with a truncating NEIL1 variant (c.821delT). In an Argentine family, the variant co-occurred with a genomic deletion of exons 2 – 11 of PMS2. Mutational signatures in tumor tissues complied with biological functions reported for NEIL1. Our results suggest that germline variants in DNA glycosylase genes may occur in a non-negligible proportion of unexplained colon polyposis cases and may predispose to tumor development.